Institutional Advancement as a Reaction to the Covid-19 Pandemic in the Tourism City of Samarkand, Uzbekistan - Wroblewski, Slawomir; Patterson, Ian; Nartov, Pavel (Journal of Tourism Management Research, 2021)
The aim of this study is to determine the effects of COVID-19 pandemic on the city of Samarkand, Uzbekistan and by adopting an institutional approach, to generate solutions that might contribute to the future development of the tourism and hospitality industries. A computer-based survey was developed and administered online using the Google Forms platform. The survey consisted of the following questions: (1) reactions to the pandemic’s influence on tourism (2) short-term recovery plans (3) long-term challenges, and (4) demographic characteristics of respondents. Surveys were distributed to email addresses of over 150 tourism managers and employees in Uzbekistan in June, 2020. A final total of 77 responses were found acceptable for analysis. Findings identified a number of institutions used as a response to the pandemic: additional state support for entrepreneurs, webinars, new investment projects, post-crisis measures, actions aimed at improving the product, and marketing campaigns to promote the tourism product. Several initiatives were instituted by Samarkand Regional Government including support for entrepreneurs and small business owners through start-up investment projects. However, overall, a lack of trust was shown between the tourism owners/providers and regional government with the majority of owners preferring to solve their own problems that were created as a result of the pandemic.